Answer: The correct option is
(A) x = -12 or x = 2.
Step-by-step explanation: We are given to solve the following quadratic equation for x :

From equation (i), we have
![x^2+10x+12=36\\\\\Rightarrow x^2+10x+12-36=0\\\\\Rightarrow x^2+10x-24=0\\\\\Rightarrow x^2+12x-2x-24=0~~~~~~~[\textup{the sum of 12 and -2 is 10 and product is -24}]\\\\\Rightarrow x(x+12)-2(x+12)=0\\\\\Rightarrow (x+12)(x-2)=0\\\\\Rightarrow x+12=0,~~~~x-2=0\\\\\Rightarrow x=-12,2.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/55tg1ni6twc90e6yp4ws9e6wq6mv8mygzo.png)
Thus, the required solution of the given equation is x = -12 or x = 2.
Option (A) is CORRECT.